The Appropriate Use of Neurostimulation: Avoidance and Treatment of Complications of Neurostimulation Therapies for the Treatment of Chronic Pain. Issue 6 (August 2014) - Deer, Timothy R.; Mekhail, Nagy; Provenzano, David; Pope, Jason; Krames, Elliot; Thomson, Simon; Raso, Lou; Burton, Allen; DeAndres, Jose; Buchser, Eric; Buvanendran, Asokumar; Liem, Liong; et al.
<x xml:space="preserve">Abstract</x> Introduction The International Neuromodulation Society (INS) has determined that there is a need for guidance regarding safety and risk reduction for implantable neurostimulation devices. The INS convened an international committee of experts in the field to explore the evidence and clinical experience regarding safety, risks, and steps to risk reduction to improve outcomes. Methods The Neuromodulation Appropriateness Consensus Committee (NACC) reviewed the world literature in English by searching MEDLINE, PubMed, and Google Scholar to evaluate the evidence for ways to reduce risks of neurostimulation therapies. This evidence, obtained from the relevant literature, and clinical experience obtained from the convened consensus panel were used to make final recommendations on improving safety and reducing risks. Results The NACC determined that the ability to reduce risk associated with the use of neurostimulation devices is a valuable goal and possible with best practice. The NACC has recommended several practice modifications that will lead to improved care. The NACC also sets out the minimum training standards necessary to become an implanting physician. Conclusions The NACC has identified the possibility of improving patient care and safety through practice modification. We recommend that all implanting physicians review this guidance and consider adapting their practice accordingly.